Author - Text - Intention: A Case Study on the Letter of James - Wischmeyer, Oda (Biblical Exegesis without Authorial Intention?, 2019)
This chapter is a plea for thinking together about the text, the author, the intentio auctoris and the intentio operis. In this field of interrelated terms, the quest for the author functions as a particular hermeneutical tool beside others that inspires a dialogue between the reader, viz., interpreter and the tex
CRIS-Team WoS Importer:2020-03-27